Effect of Unpuddled Transplanting on the Growth and Yield of Dry Season Rice (Oryza sativa L.) in High Barind Tract (The Agriculturists, 2015)
Conservation tillage technology not only protects natural resources but also provides some economic leverage. The present investigation evaluated two puddle tillages (i) conventional tillage (CT) and (ii) single pass wet tillage (SPWT) and two unpuddled tillages(iii) strip tillage(ST) and (iv) bed planting (BP) to establish rice in the High Barind Tract, Godagari, Rajshahi during aus 2010 and boro 2011 season. The CT option incurred higher cost compared to other tillage treatments due to more fuel and labour used in land preparation. Minimum tillage (SPWT, ST and BP) saved about 30-54% fuel consumption and 40-49% labour requirement compared to CT in land preparation. Labour did not face much difficulty to transplant seedling in unpuddled fields. However, unpuddled establishment required more labor for weeding compared to puddle one. Bed planting in aus gave significantly lower grain yield than other establishment methods. However, in boro season, all the tested tillage methods produced similar yield. In both seasons, CT showed the highest input costs due to more number of tillage passes and fuel requirement in land preparation. As a consequence, SPWT, ST and BP appeared to be more profitable than CT both in aus and boro rice.The Agriculturists 2014; 12(2) 91-97